Early Career Members at the ERS International Congress London 2016: Early Career Forum. Issue 4 (December 2016) - Bos, Lieuwe D.; Bartel, Sabine; Ojanguren Arranz, Inigo; Kahn, Nicolas C.; Mathioudakis, Alexander G.; Flood, Emma; Petrarca, Laura; Singanayagam, Aran; Hardavella, Georgia
This year's ERS International Congress was, as always, well organised, providing participants with a good mixture of translational and clinical science. At Congress, the Junior Member title was changed to the Early Career Member (ECM) with the ERS defining an ECM as anyone under age of 40 years. Some of the newly titled "ECM Committee" have collated some interesting points that occurred during Congress for their assemblies, which should be of interest to all members. The @ERSTalk ECM Committee present highlights from #ERSLDN16 for Early Career Members http://ow.ly/tRYH305Owmz